Ijarah Collaborative Service Model in Sharia Banking - Chaidir Iswanaji; Aziz Muslim; M. Zidny Nafi' Hasbi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
Ijarah is a contract for the transfer of usufructuary rights over goods or services, through payment of rental wages, without being followed by a transfer of ownership of the goods themselves. The context of ijarah in Islamic banking is a lease contract in which a bank or financial institution leases equipment to one of its customers based on a definite predetermined cost. The research method is qualitative with a comparative study approach. Data collection techniques include observation, documentation, and deep interviews. The object of this research was carried out in the Yogyakarta area. The findings of the ijarah case presented in this study indicate that the services created jointly by customers, service organizations (Islamic banks), and assisting parties divide their roles into sub-roles assigned to individuals. This research provides a basic understanding of the development of a sharia service model, which can complement the current IFM to holistically capture both economic transactions and service elements, which are currently prevailing in the Islamic banking market.